Spatiochemical Analysis of Heavy Metal Contamination in Water Sources from Langalanga Mining Site, Bali L.G.A, Taraba State, Nigeria - David Musa Garkida; Daniel Emeka Oruenye; Yushau Ahmed Mohammed; Delphine David Leila (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Mining activities in developing nations like Nigeria drive economic growth but often result in environmental degradation, particularly through heavy metal contamination of water resources. This study assessed the concentrations of heavy metals, including cadmium (Cd), lead (Pb), chromium (Cr), and iron (Fe) in water samples from the Langalanga mining site in Bali L.G.A, Taraba State, Nigeria. Using Atomic Absorption Spectrophotometry (AAS), the analysis revealed significant exceedances of World Health Organization (WHO) and Nigerian Standard for Drinking Water Quality (NSDWQ) limits for iron (1.0465 ppm vs. 0.3000 ppm) and lead (0.0348 ppm vs. 0.0100 ppm). While manganese (Mn) and nickel (Ni) levels remained below thresholds, anomalies such as negative values for copper (Cu) and zinc (Zn) in control samples indicated potential analytical challenges. The findings underscore the urgent need for stricter regulatory enforcement and remediation measures to mitigate health risks, such as neurological disorders and liver damage, associated with prolonged exposure. This study highlights the dual necessity of standardized methodologies and site-specific approaches in addressing mining-related water pollution in Nigeria.